Rural Marketing : A Study of Consumer Behaviour - Lokhande, M. A. (Indian Journal of Marketing, 2004)
Everybody of us is a consumer. We need a variety of goods and services right from our birth to death. Because, of marketing, we can have what we need. Marketing is a process through which both the buyer and seller give, something (e.g. goods, services, money etc.) to each other for maximum possible satisfaction. Nowadays, Rural Marketing is gaining importance. All the FMCG companies viz. HLL, Pepsi, Coca Cola, Britannia, Colgate Palmolive, Samsung etc. are concentrating their marketing activities in rural markets. Why? Because of socio-economic changes and huge market of more than 80 million households which will increase to 111 million households by 2007 (NCEAR report). Rural Consumer has become enough aware about his needs and up gradation of his standard of living. Information technology, Govt. Policies, corporate strategies and satellite communication are the factors responsible for development of Rural Marketing. Let us look at the potential of rural markets. Rural consumption share in popular soaps is 48%, tooth pastes 24%, talcum powder-17%, cold medicines-42%, Batteries-52% etc. The Market for Packaged food items of Rs. 20,000 crores is growing at 2.5% per year. It is interesting to understand the various aspects of the rural markets and consumption patterns.